Comparative transcriptomic reveals the molecular mechanism of maize hybrid Zhengdan538 in response to water deficit. Issue 6 (21st November 2022) - Zhang, Fengqi; Ding, Yong; Zhang, Jun; Tang, Minqiang; Cao, Yanyong; Zhang, Lanxun; Ma, Zhiyan; Qi, Jianshuang; Mu, Xinyuan; Xia, Laikun; Tang, Baojun
Abstract: Heterosis, known as one of the most successful strategies for increasing grain yield and abiotic/biotic stress tolerance, has been widely exploited in maize breeding. However, the underlying molecular processes are still to be elucidated. The maize hybrid "Zhengdan538" shows high tolerance to drought stress. The transcriptomes of the seedling leaves of its parents, "ZhengA88" and "ZhengT22" and their reciprocal F1 hybrid under well‐watered and water deficit conditions, were analyzed by RNA sequencing (RNA‐Seq). Transcriptome profiling of the reciprocal hybrid revealed 2994–4692 differentially expressed genes (DEGs) under well‐watered and water‐deficit conditions, which were identified by comparing with their parents. The reciprocal hybrid was more closely related to the parental line "ZhengT22" than to the parental line "ZhengA88" in terms of gene expression patterns under water‐deficit condition. Furthermore, genes showed expression level dominance (ELD), especially the high‐parental ELD (Class 3 and 5), accounted for the largest proportion of DEGs between the reciprocal F1 hybrid and their parental lines under water deficit. These ELD genes mainly participated in photosynthesis, energy biosynthesis, and metabolism processes. The results indicated that ELD genes played important roles in hybrid tolerance to water deficit. Moreover, a set of important drought‐responsive transcription factors were found to be encoded by the identified ELD genes and are thought to function in improving drought tolerance in maize hybrid plants. Our results provide a better understanding of the molecular mechanism of drought tolerance in hybrid maize.